Assessing Female’s Experiences and Perceptions of Public Open Spaces in Pokhara Metropolitan City, Nepal - Pokharel, Ramjee Prasad (Geographical Journal of Nepal, 2025)
Public open spaces (POS) play a pivotal role in urban environments, offering a many of benefits ranging from recreational to ecological. These spaces are not only essential for the public but also hold particular significance for female users. This study investigates and analyses the experience and perceptions of female users groups toward public open spaces (POS) in a metropolitan area. It explores how users who may experience varying levels of satisfaction perceive the aesthetics of POS. Public open spaces are vital urban sites, and this study aims to identify the perceptions of female POS users within these spaces. Factors such as age, caste, occupation, and level of education in determining the levels of satisfaction are taken into consideration. Attractions that are naturally appealing, culturally significant, psychologically safe, and visually decorative have been considered as parameters for measuring the perceptions of POS. The study concludes with insights drawn from the experiences of female users regarding the current condition of public open spaces in the city. It reveals a strong connection between the POS and its female users. However, the current management of these spaces is inadequate. To better meet the user expectations, it is essential for concerned stakeholders to focus on improving management practices and developing the necessary infrastructure in the POS of Pokhara Metropolitan City.